STUDY ON POTENTIALS OF PINEAPPLE SKIN EXTRACT FERMENTED WITH Lactobacillus casei AS A PROBIOTIC BEVERAGE BY IN VIVO - Samsul Rizal; Samsu Udayana Nurdin; Suharyono Suharyono; Marniza Marniza (Jurnal Agroindustri, 2020)
The objectives of the research are to learn the effect of fermented drink of pineapple peel extract fermented by Lactobacillus casei toward microflora of digest of Sprague Dawley rats and to know its potential as a probiotic drink.  The treatment compiled by Randomized Complete Block Design (RCBD) with six repetitions.  Eighteen male weanlings Sprague Dawley rats are divided into three groups.  Each group consists of six rats and has different treatments.  One group was given a lactate fermented beverage of pineapple skin extract, one group was given a drink of pineapple skin extract that was not fermented and the other group was given water as a control. The parameters observed include total lactic acid bacteria and total coliform of the digest. The research showed that the provision of lactic acid fermentation drinks produced higher total lactic acid bacteria (LAB) and lower total coliform of digest than the provision of the non-fermented drink of pineapple peel concentrate and provision of water as the control on the rats model. Total LAB in digestion of rats fed fermented pineapple concentrate drinks was 1,6 x 1012 cfu/gram while total coliform was 3,7 x 1011 cfu/gram. The pineapple skin concentrate fermented by Lactobacillus casei is potential as a probiotic drink because of its ability to inhibit pathogenic bacteria